Climate Change: Reviewing Indonesia's Compliance with the Paris Agreement on Commitments to Reduce Emissions - Imawan, Riswandha (Widya Yuridika, 2023)
Climate change is a threat to current and future generations. The main cause of climate change is the use of fossil fuels such as coal, oil and gas. Amidst the international community's concerns about climate change, the use of fossil fuels has increased, including in Indonesia. This research aims to analyse Indonesia's compliance with the 2015 Paris Agreement. Indonesia as a country that binds itself to the Paris Agreement has a commitment to reduce emissions in an effort to mitigate climate change. This research analysed using regime compliance theory. The research method used is juridical-normative. The results showed that Indonesia complies with the Paris Agreement regime because it fulfils three indicators in the regime compliance theory, namely output, outcome, and impact.